2022
DOI: 10.1093/noajnl/vdac082
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of the immune system predicts clinical outcomes in glioblastoma immunotherapy: A systematic review and meta-analysis

Abstract: Background Biological differences based on sex have been documented throughout the scientific literature. Glioblastoma (GBM), the most common primary malignant brain tumor in adults, has a male sex incidence bias, however, no clinical trial data examining differential effects of treatment between sexes currently exists. Method We analyzed genomic data, as well as clinical trials, to delineate the effect of sex on the immune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Additionally, an aspect outside of the scope of this study but still of pressing interest is the extent to which sex differences in antigen-presenting cells are present and affect T cell behavior. A meta-analysis on GBM clinical trials employing autologous dendritic cells showed that female patients had a more robust survival advantage compare to male patients, providing a rationale to understand underlying mechanisms (43). Taken together, our study identifies T cells as a critical component driving sex differences in GBM progression and a male-biased T cell exhaustion state that could potentially interrogate sex-specific immunotherapy responses in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an aspect outside of the scope of this study but still of pressing interest is the extent to which sex differences in antigen-presenting cells are present and affect T cell behavior. A meta-analysis on GBM clinical trials employing autologous dendritic cells showed that female patients had a more robust survival advantage compare to male patients, providing a rationale to understand underlying mechanisms (43). Taken together, our study identifies T cells as a critical component driving sex differences in GBM progression and a male-biased T cell exhaustion state that could potentially interrogate sex-specific immunotherapy responses in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Females have been found to have a more active adaptive immune system, and thus, differential immune responses and sensitivities between sexes have been implicated in sexual dimorphism in GBM ( 37 39 ). In a study by Shireman et.…”
Section: Sex-specific Gbm Immune System Characteristicsmentioning
confidence: 99%
“…Retrospective and prospective studies have previously identified potential prognostic and predictive factors grounded in sex differences. Sex differences have been noted in anti-epileptic management [ 70 ], chemotherapy [ 12 , 71 ], and immunotherapy [ 11 , 17 ] ( Table 3 ). Looking ahead at the potential future results of omic analyses will therefore involve looking back at current and previous trials wherein a biospecimen was/is being collected to examine where future conclusions may originate from ( Table 5 ) and how this bedside data connects to bench data, including tissue culture and animal studies.…”
Section: Omics and Biospecimen Analysismentioning
confidence: 99%
“…A recent systematic review and meta-analysis lent further evidence about existing sexual dimorphism of the immune system as related to clinical outcomes in glioblastoma immunotherapy. Upon analyzing genomic data and clinical trials looking at the effect of sex on the immune system and GBM outcome following immunotherapy, the authors identified that females exhibited enriched immunological signatures on gene set enrichment analysis, which correlated with survival advantage as compared to males, particularly as related to vaccine-based immunotherapy [ 17 ]. An increasing quantity of data is emerging on the relationship between tumor mutational burden (TMB) and its role as a prognostic marker, and gender, with male and female patients exhibiting differential TMB in some cancers concerning prognosis [ 78 ].…”
Section: Omics and Biospecimen Analysismentioning
confidence: 99%
See 1 more Smart Citation